2016
DOI: 10.18616/is.v5i1.1915.117-128
|View full text |Cite
|
Sign up to set email alerts
|

Perfil clínico de neonatos internados em uma UTI do sul catarinense

Abstract: Estudo com objetivo de identificar o Perfil Clínico de Neonatos Internados em uma Unidade de Terapia Intensiva Neonatal (UTI-N), pesquisa de abordagem quantitativa, descritiva. O estudo foi desenvolvido em um Hospital de Médio Porte da Região Sul de Santa Catarina no município de Criciúma- SC. A amostra estudada foi através de documentos arquivados no local do estudo, a Unidade de Terapia Intensiva Neonatal, a análise dos dados foi realizada a partir da base de dados, através da ordenação, classificação e anál… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
1
2
0
2
Order By: Relevance
“…A previous study, published in 2016, also showed a higher frequency of this classification of prematurity in Brazil, in which the late ones reached 74% of births, representing three quarters of all premature newborns in the country. 5 As in other studies, 4,6 here, males were more frequent among hospitalized patients. In a comparative approach, a study undertaken in the Netherlands showed that male newborns were associated with an increased risk of fetal distress, while females have a protective effect for this outcome, 7 which could contribute to the higher frequency of premature newborns among the male gender.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…A previous study, published in 2016, also showed a higher frequency of this classification of prematurity in Brazil, in which the late ones reached 74% of births, representing three quarters of all premature newborns in the country. 5 As in other studies, 4,6 here, males were more frequent among hospitalized patients. In a comparative approach, a study undertaken in the Netherlands showed that male newborns were associated with an increased risk of fetal distress, while females have a protective effect for this outcome, 7 which could contribute to the higher frequency of premature newborns among the male gender.…”
Section: Discussionsupporting
confidence: 78%
“…There is a high prevalence of sepsis in our population, and the frequency of this complication was similar between groups, results also evidenced in other studies. 4,14 Newborns hospitalized in the NICU undergo various invasive treatments and procedures that increase susceptibility to infections. 18 Neonatal sepsis (early and late) associated with the immune fragility of the premature neonate, makes it one of the main causes of mortality for this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partos prematuros coloca o recém-nascido (RN) numa categoria de grande risco nutricional; nesse sentido, a alimentação representa um contínuo desafio para os responsáveis pela nutrição 24 .…”
Section: Resultados E Discussõesunclassified
“…6 Existe uma complexa relação entre fatores sociodemográficos, condições de gestação, parto e pós-parto que influenciam na morbimortalidade e internação dos recém-nascidos, sendo assim, é essencial conhecer esses fatores de risco, visto que muitos são evitáveis e constituem um grave problema de saúde pública. 7,8 É fundamental oportunizar o acesso das mulheres aos serviços de saúde precocemente na gestação. Desde 2000, diversas estratégias, planos e políticas para promover e minimizar a morbimortalidade foram desenvolvidas, como o Programa de Humanização no Pré-natal e Nascimento (PHPN), a Iniciativa Hospital Amigo da Criança (IHAC), e o Pacto Nacional pela Redução da Mortalidade Materna e Neonatal.…”
Section: Introductionunclassified